1996
DOI: 10.1111/j.1432-1033.1996.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Up‐Regulates and Prostaglandin E2 Down‐Regulates the Expression of Pancreatic‐Type Phospholipase A2 and Prostaglandin‐Endoperoxide Synthase 2 in Uterine Stromal Cells

Abstract: It is well known that arachidonic acid, as a substrate of prostaglandin G/H synthase (PGHS), is converted into prostaglandins of the two-series. In this work, we attempted to determine whether arachidonic acid and prostaglandin E2 might regulate the expression of PGHS and the pancreatic-type phospholipase A2 (PLA2I), which may be involved in the liberation of arachidonic acid from membrane phospholipids. For this purpose, we used the uterine stromal cell line UIII, which produces prostaglandin E2 and expresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…Increased production of PG in various tissues after stimulation by polyunsaturated fatty acids has been previously reported in rat uterine stromal cells [49] and in endometrial cells from the late-pregnant ewes [25]. In our study, AA increased levels of COX-2 and cPLA 2 after 48 hours of incubation and these results were in agreement with what previously shown in bovine endometrial cells [50].…”
Section: Discussionsupporting
confidence: 95%
“…Increased production of PG in various tissues after stimulation by polyunsaturated fatty acids has been previously reported in rat uterine stromal cells [49] and in endometrial cells from the late-pregnant ewes [25]. In our study, AA increased levels of COX-2 and cPLA 2 after 48 hours of incubation and these results were in agreement with what previously shown in bovine endometrial cells [50].…”
Section: Discussionsupporting
confidence: 95%
“…For instance, the induction of COX-2 expression in cytokine-stimulated mast cells was not affected by several PLA 2 and COX inhibitors, indicating that the regulatory mechanism was PG-independent (41). Arachidonic acid up-regulated, whereas PGE 2 down-regulated, the induction of COX-2 in uterine stromal cells (42). IL-1␤-induced arachidonic acid release and subsequent COX-2-dependent PGE 2 generation were augmented significantly in sPLA 2 -transfected compared with normal CHO-K1 cells, without accompanying changes in cPLA 2 and COX-2 expression (20).…”
Section: Fig 3 Effects Of Cox and Cpla 2 Inhibitors On Pge 2 Generamentioning
confidence: 89%
“…It seems likely that at short times, the free AA may act as a signaler rather than an intermediary metabolite. As a matter of fact, it has been suggested that exogenous AA up-regulates the expression of COX-2 in uterine stromal cells (38). The induction is not due to conversion of AA to prostaglandin by COX-1 because it occurs even in the presence of aspirin, a well known inhibitor of COX activity.…”
Section: Discussionmentioning
confidence: 99%